PI/NCC carbon membrane : effect of additives loading towards hydrogen separation - Norazlianie, Sazali; R., Mamat; J. P., Siregar; T., Gunawan; W. N. W., Salleh; N. A. H. M., Nordin (IOP Publishing, 2020)
Incorporating thermally labile polymer-based additives is a facile and practical approach in developing superior carbon membranes. In this study, three different thermally labile polymers, microcrystalline cellulose (MCC), nanocrystalline cellulose (NCC), and polyvinylpyrrolidone (PVP), were introduced separately to P84-copolyimide (PI) solution as additive and their impact on membrane performance were investigated. Firstly, NCC was added as the membrane pore former for hydrogen gas (H2) separation. The addition of NCC significantly increased pore channels in the membrane, hence contributed to high gas permeance and selectivity. The tests involving pure H2 and N2 permeation were carried out at room temperature. Carbon membranes carbonized at a final temperature of 800°C with the heating rate of 3°C/min under Ar flow achieved the greatest H2/N2 selectivity of 434.68±1.39, hence proving the potential of NCC as a good additive.